Rebellious uniform - Farmer, Mark Ross (Rhodes University, Faculty of Humanities, Department of Fine Art, 2012)
In this thesis, I focus on adolescent teens at Kingswood College High School, where I am currently employed as a student assistant in Grahamstown. I form part of a networked hierarchy at Kingswood College whereby I am expected to perform duties which require me to uphold discipline, forge respect and act as a mentor to students. Within this complex role I am mindful of the power dynamics within the school and my focus is on how the students at Kingswood College in some instances challenge them. Regulations in regard to uniforms and in regard to the arrangement of each learner's belongings insist on the sublimation/sacrificing of an individual identity in favour of an institutional one. Thus tiny departures from those norms, slight transgressions, might be understood as small rebellions which the boarder stages against disciplinary structures and the conformity demanded of him or her. I am particularly interested in these transgressions. In this thesis I attempt to unravel the complexities associated with such idiosyncrasies and how they play out amongst adolescent teens.
Keywords: High school students -- South Africa -- Eastern Cape -- Discipline; Teenagers -- South Africa -- Eastern Cape -- Conduct of life; Teenagers -- Education (Secondary) -- South Africa; School discipline